Employees Attrition Detection using PSONN (International Journal of Innovative Research in Computer Science & Technology, 2019)
Raw materials, intermediate goods and finished  goods are termed as inventories while considering it as portion of  business’s assets which can be considered as prepared or are  prepared for sale. One of the suitable solutions is to design  optimal inventory model. Major concern of industry is to design  suitable inventory model. Some of the existing inventory  management research works are discussed in literature. But this  field is still a big area of interest. Many research works uses  artificial intelligence models for inventory management. One amongst the area for inventory management is worker behavior  in a company. So, employees are taken into account to be as an  inventory that contributes in growth of an organization.  Employee Attrition may be a big issue for the organizations  specially once trained, technical and key staff leave for a far  better chance from the organization. This leads to loss to  interchange a trained worker. Therefore, we use the present and  past worker data to analyze attrition behavior of employees.
Keywords: Raw materials; Inventories; Inventory Management; Artificial Intelligence